Kedudukan Dan Pertanggung Jawaban Pidana BUMN Sebagai Korporasi Terhadap Kerugian Negara - Mamduh, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The globalization and the development of scine, technology and all aspect of life that requires all of scienes that moves adaptively to cope outside of the positive impact. A crime that was originally done simply, is getting mire and more complicated and systematically, this is what is called the “crime globalization”. In the fact, law as a sciene, must be able to adapt with all the currents situation, as a mean to overcrime the “crime globalitation” especially the Responsibillity of BUMN as a Corporation, when doing something that is detrimental to the state’s finances. The research method used in this article is a normative judicial. The results of the study conclude in the corporate criminal liability policy that it cannot be justified the loss of a transaction that becomes a loss or automatically becomes a loss to the State, because the wealth of BUMN is not the wealth of State, but the wealth of the separated Stated.